In‐memory integration of existing software components for parallel adaptive unstructured mesh workflows. (27th April 2018) - Smith, Cameron W.; Granzow, Brian; Diamond, Gerrett; Ibanez, Daniel; Sahni, Onkar; Jansen, Kenneth E.; Shephard, Mark S.
Summary: Reliable mesh‐based simulations are needed to solve complex engineering problems. Mesh adaptivity can increase reliability by reducing discretization errors but requires multiple software components to exchange information. Often, components exchange information by reading and writing a common file format. This file‐based approach becomes a problem on massively parallel computers where filesystem bandwidth is a critical performance bottleneck. Our approach using data streams and component interfaces avoids the filesystem bottleneck. In this paper, we present these techniques and their use for coupling mesh adaptivity to the PHASTA computational fluid dynamics solver, the Albany multi‐physics framework, and the Omega3P linear accelerator frequency analysis applications. Performance results are reported on up to 16, 384 cores of an Intel Knights Landing‐based system.